1997
DOI: 10.1128/iai.65.5.1606-1614.1997
|View full text |Cite
|
Sign up to set email alerts
|

Acquired immune responses to the N- and C-terminal regions of Plasmodium vivax merozoite surface protein 1 in individuals exposed to malaria

Abstract: In this study, we evaluated the naturally acquired immune response to Plasmodium vivax merozoite surface protein 1 (PvMSP1) in individuals with recent clinical episodes of malaria from the state of Pará, Brazil. Ten recombinant proteins representing the first 682 amino acids (aa) of the N-terminal region and one representing the final 111 aa of the C-terminal region were expressed in Escherichia coli as glutathione S-transferase fusion proteins. Both of these regions have been suggested as candidates for devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
11

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 38 publications
4
47
0
11
Order By: Relevance
“…Plasmas or cells from individuals were tested for reactivity with the native or recombinant TS by proliferation assay and ELISA essentially as described by Soares et al (1997). For the proliferation assay, arithmetic mean cpm for each set of triplicate wells was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmas or cells from individuals were tested for reactivity with the native or recombinant TS by proliferation assay and ELISA essentially as described by Soares et al (1997). For the proliferation assay, arithmetic mean cpm for each set of triplicate wells was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The isotype content of sera from individuals with defined clinical states of resistance or susceptibility to malaria has been investigated in several tropical countries. Those studies also revealed that the cytophilic antibody subclasses predominated in protected subjects (63)(64)(65). It has also been reported that the antibody was necessary to eliminate a blood-stage malaria parasite infection (66).…”
Section: Discussionmentioning
confidence: 85%
“…Homologue PvMSP1 a 200 kDa protein expressed on the surface of P. vivax merozoite, is also a current vaccine candidate against asexual blood stages [17]. Studies on the naturally acquired humoral immune responses against P. vivax MSP1, showed that MSP1 C-terminal fragment of P. vivax (PvMSP1 19 ) is the most immunogenic portion of the molecule and evidence suggests that immunodominant domains interacting with protective antibodies are related to a structure also containing two epidermal growth factor (EGF)-like domains, like in PfMSP1 19 [18,19]. Furthermore, vaccine trials with PvMSP1 19 and PvMSP1 33 have succeeded in protecting monkeys and it has been shown that a large proportion of individuals naturally exposed to P. vivax transmission, develop specific antibodies to PvMSP1 19 [20][21][22].…”
Section: Introductionmentioning
confidence: 99%